RDF-based Web Information Integration System : A Travel System Use Case - HOUNGUE, Yénukunmè Pélagie Elyse; SAGBO, Romaric Kouessi (My University, 2018)
Enterprises are continually faced with the challenge of integrating heterogeneous systems with incompatible interfaces, data structures (structured sources: e.g. relational databases, semi-structured sources: e.g. XML or unstructured documents: e.g. texts), access mode and technologies. When companies adopt SOA (Service Oriented Architecture), that provides an alternative to traditional design of applications by allowing a designer to assemble and compose existing services that implement the functions of a given application domain, they realize that there is a significant risk that Web services only do not solve the problem of compatibility in the data. Our paper gives a solution to these issues by setting up a virtual data integration system on top of heterogeneous data sources. A multilayer application system is designed and eases data extraction and combination using RDF technology. Based on a given application service request, matching algorithms allow rewriting a well-known application service in ADPS (Abstract Data-Providing Services). The ADPS are functionalities available in enterprises belonging to the same ecosystem, which are easy to implement by data sources. Application rewriting aims to facilitate their implementation.
Keywords: RDF; Web service; service composition; data; integration; Data-Providing Service